The day I saw your heart [videorecording (DVD)] - Devoldère, Jennifer. 1974-; Kramer, Jody; Laurent, Mélanie, 1983-; Blanc, Michel, 1952-; Loiret-Caille, Florence (Film Movement series, 2012)
Eli, who's about to be 60, is expecting a baby with his new wife. Upon hearing this news, his two grown daughters, Dom, who is trying to adopt, and Justine, who flits from one boyfriend to the next, are shocked. To get closer to Justine, whom he has never gotten along with, Eli has the bright idea of making friends with all of her exes ... without her knowledge. But when Justine falls in love again and Eli is about to ruin everything, this family is on the verge of falling apart.